2022
DOI: 10.1038/s41598-021-04531-x
|View full text |Cite
|
Sign up to set email alerts
|

Better COVID-19 Intensive Care Unit survival in females, independent of age, disease severity, comorbidities, and treatment

Abstract: Although male Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) patients have higher Intensive Care Unit (ICU) admission rates and a worse disease course, a comprehensive analysis of female and male ICU survival and underlying factors such as comorbidities, risk factors, and/or anti-infection/inflammatory therapy administration is currently lacking. Therefore, we investigated the association between sex and ICU survival, adjusting for these and other variables. In this multicenter observational coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Males typically experience more frequent lower respiratory tract infections [ 112 ] and, in the case of influenza A and B viruses, RSV, SARS-CoV, and other sources of community-acquired pneumonia, more severe disease compared to females [ 113 , 114 ]. Similarly, with SARS-CoV-2 infection, males are hospitalized [ 8 , 115 ], are admitted to intensive care unit (ICU) [ 8 , 116 ] and die [ 117 , 118 ] more often, although infection rates appear to be similar to those of women [ 119 ]. Sex-disaggregated estimates of the infection fatality ratio show consistently higher fatality rates among males in every age category [ 8 , 9 ].…”
Section: Host Factorsmentioning
confidence: 99%
“…Males typically experience more frequent lower respiratory tract infections [ 112 ] and, in the case of influenza A and B viruses, RSV, SARS-CoV, and other sources of community-acquired pneumonia, more severe disease compared to females [ 113 , 114 ]. Similarly, with SARS-CoV-2 infection, males are hospitalized [ 8 , 115 ], are admitted to intensive care unit (ICU) [ 8 , 116 ] and die [ 117 , 118 ] more often, although infection rates appear to be similar to those of women [ 119 ]. Sex-disaggregated estimates of the infection fatality ratio show consistently higher fatality rates among males in every age category [ 8 , 9 ].…”
Section: Host Factorsmentioning
confidence: 99%
“… 9 In patients with covid-19 who required admission to the intensive care unit and vital organ support, female participants were still 37% less likely than male participants to die in the intensive care unit, independent of age, severity of the acute critical illness, lifestyle factors, and comorbidities. 26 In our study, female participants had a 35% lower odds of death than male participants while in hospital. Whether this difference between the sexes is the same or greater than would be expected in the general population, where male individuals have a shorter life expectancy, is unclear.…”
Section: Discussionmentioning
confidence: 48%
“…This result is in line with previous findings showing persistent sex differences even after adjusting for the Acute Physiology and Chronic Health Evaluation II (APACHE II) score, indicating the severity of acute illness. 26 Previous research, however, has shown that the association between peak levels of C reactive protein and adverse outcomes in covid-19 is stronger in male individuals. 47 The higher risk of severe disease in male individuals among patients admitted to hospital for covid-19 might also be explained by their later presentation to hospital than female individuals.…”
Section: Discussionmentioning
confidence: 96%
“…However, their review highlighted a lack of gender-sensitive awareness in the translation of clinical research findings into gender-specific treatment regimens, guidelines, and preventive strategies, as well as in the development of gender-oriented health policies. Similarly to other diseases, COVID-19 exhibits a high degree of heterogeneity in its clinical course and disease severity [ 50 , 51 ]. Many factors can trigger the differences between individuals, including their clinical condition, access to healthcare services and preventive programs, and the local epidemiological context [ 14 , 23 , 25 , 27 , 48 ].…”
Section: Discussionmentioning
confidence: 99%